Analysis of Healthcare Workers' Perceptions of the Quality of Training and Professional Development at Simalingkar Community Health Centers (Puskesmas) in 2024 - Lubis, Irwansyah; Zahra Putri Purba , Anita; Aldona, Cindy; Dina, Putri; Sari Siregar, Meida (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Training and professional development are crucial factors in improving the quality of human resources (HR) in the healthcare sector. This component is crucial for ensuring that healthcare workers have the skills and knowledge necessary to provide safe and effective healthcare services. This study used a qualitative descriptive approach to understand healthcare workers' perceptions of the quality of training and professional development at Simalingkar Community Health Centers. The study subjects were healthcare workers selected based on their experience participating in training and professional development. The study found that healthcare workers at Simalingkar Community Health Centers have positive perceptions of training and professional development, which includes the use of health applications and curative treatment methods. The planning process involves regular meetings with the government and is supported by the Regional Budget (APBD) and the Regional Budget (BOK). Training has been shown to improve work quality, and mini-workshops are used for evaluation and agreement on next steps. The success of training is influenced by management support, resources, organizational culture, government policies, technology, and collaboration with educational institutions. This study concludes that the training and professional development program at Simalingkar Community Health Center has demonstrated a positive impact on the performance of healthcare workers and the quality of services provided. However, the program's success is influenced by various internal and external factors, including the individual, training methodology, work environment, and training needs.